Culinary Product Innovation Strategy Micro, Small and Medium Entreprise in The New Normal Era - Dewi Nurbaiti; Nur Fitri Rahmawati; Suparman; Rousdy Safari Tamba; Thamrin (Ilomata International Journal of Management, 2021)
The existence of a corona virus epidemic or Covid-19 that lasted a long time in several countries, one of which in Indonesia has a negative impact on the Micro and Small Medium Enterprises (MSMEs). The impact that occurred was the decline in turnover due to the reduced number of buyers, where many MSMEs had to close their businesses. When entering the new normalcy era or the New Normal era, the SMEs will open their businesses again but get new challenges in terms of product innovation. Innovation is needed to make a business survive in the new normal era, one of which is innovation in terms of product types. The purpose of this study is to produce recommendations for SMEs in determining the right product innovation strategy in the New Normal era. This study raises the formulation of the problem of how the SME product innovation strategy in the current era of New Normal. The method used in this study is a qualitative research method with data collection techniques through network interviews and descriptive data analysis techniques, with research informants who are SMEs in East Jakarta. The results of this study indicate that in the New Normal era, the SMEs are implementing a product innovation strategy by changing the shape of the product in the same type (changing shape) and also changing the type of product that is different from the previous product (changing type). By implementing the two product innovation strategies, SMEs can still compete in the New Normal era at this time. Recommendations from this research are expected to be used by SMEs to be more innovative in producing culinary products so they can survive in the New Normal era.